2017
DOI: 10.1080/00365521.2017.1342140
|View full text |Cite
|
Sign up to set email alerts
|

Non-specific abdominal pain remains as the most common reason for acute abdomen: 26-year retrospective audit in one emergency unit

Abstract: NSAP is still the main differential diagnostic problem in the ED. Except acute appendicitis, distribution of specific diagnoses causing AAP remained rather stable through 26-year audit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 16 publications
0
43
1
6
Order By: Relevance
“…AA is still the most common reason for AAP and the ratio of AA in patients with AAP is between 11-23% (17). The ratio of AA in this study was 32% (15 of 45 patients) which was higher than the literature.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…AA is still the most common reason for AAP and the ratio of AA in patients with AAP is between 11-23% (17). The ratio of AA in this study was 32% (15 of 45 patients) which was higher than the literature.…”
Section: Discussioncontrasting
confidence: 74%
“…It was concluded that the RAMRI was significant and hopeful because the radiological analysis duration was shorter and it provided enough information. There are some disadvantages of the method; the patients who have claustrophobia and hearth battery are not allowed for MRI (17). Despite short analysis duration, diagnostic images may not be handled because of pain.…”
Section: Discussionmentioning
confidence: 99%
“…For CT examinations of the head, these included acute intracranial hemorrhage and acute cerebral infarction; for CTA-HN, these included intracranial arterial thrombosis, occlusion or high-grade stenosis (> 70%) of the carotid or vertebral arteries, 21 and dural venous sinus thrombosis; for CTPA, these included pulmonary artery emboli; and for CT examinations of the abdomen and pelvis, these included acute appendicitis, diverticulitis, bowel obstructions, ureteric calculi and acute aortic syndrome. [22][23][24] Findings that were incidental and of doubtful clinical significance were not considered as new findings (e.g., brain atrophy and microan gio pathic ischemic change typical for age on CT examinations of the head, mild carotid stenosis [< 30%] on CTA-HN, dependent subsegmental atelectasis and incidental pulmonary nodules < 6 mm on CTPA, and cholelithiasis, diverticulosis and small fat-containing hernias on CT examinations of the abdomen and pelvis).…”
Section: Data Collection and Extractionmentioning
confidence: 99%
“…The leading gastrointestinal reason for an emergency visit in 2012 was a functional or motility disorder, diagnosed in 11.2% of all gastrointestinal patients [13]. A recent long-term study (1980–2012) of emergency room visits in Finland showed non-specific abdominal pain was the most common diagnosis [14]. A recent survey study of 1924 patients with a history of gastrointestinal symptoms showed 43% were not formally diagnosed with IBS despite meeting the diagnostic criteria for this condition [15].…”
Section: Epidemiology Of Chronic Pancreatitismentioning
confidence: 99%